At-Line Cellular Screening Methodology for Bioactives in Mixtures Targeting the α7-Nicotinic Acetylcholine Receptor. (June 2016) - Otvos, Reka A.; Mladic, Marija; Arias-Alpizar, Gabriela; Niessen, Wilfried M. A.; Somsen, Govert W.; Smit, August B.; Kool, Jeroen
The α7-nicotinic acetylcholine receptor (α7-nAChR) is a ligand-gated ion channel expressed in different regions of the central nervous system (CNS). The α7-nAChR has been associated with Alzheimer's disease, epilepsy, and schizophrenia, and therefore is extensively studied as a drug target for the treatment of these diseases. Important sources for new compounds in drug discovery are natural extracts. Since natural extracts are complex mixtures, identification of the bioactives demands the use of analytical techniques to separate a bioactive from inactive compounds. This study describes screening methodology for identifying bioactive compounds in mixtures acting on the α7-nAChR. The methodology developed combines liquid chromatography (LC) coupled via a split with both an at-line calcium (Ca 2+ )-flux assay and high-resolution mass spectrometry (MS). This allows evaluation of α7-nAChR responses after LC separation, while parallel MS enables compound identification. The methodology was optimized for analysis of agonists and positive allosteric modulators, and was successfully applied to screening of the hallucinogen mushroom Psilocybe Mckennaii . The crude mushroom extract was analyzed using both reversed-phase and hydrophilic interaction liquid chromatography. Matching retention times and peak shapes of bioactives found with data from the parallel MS measurements allowed rapid pinpointing of accurate masses corresponding to the bioactives.